M. Herzfeld, Subversive Archaism. Troubling Traditionalists and the Politics of National Heritage, Duke University Press, Durham, 2022, 239 pp. - Pantellaro, Cristina (L'Uomo società tradizione sviluppo, 2024)
No abstract